Post-hoc analysis of real-world retrospective study on neoadjuvant chemotherapy combined with immunotherapy for stage I-III non-small cell lung cancer - Shao, Yanchi; Wang, Shenghan; Yu, Yingchun; Yang, Weiwei; Song, Lei; Wuyuntanghesi,; Zhao, Yanbin (Frontiers in Immunology, 2026)
Background and purposeReal-world data on neoadjuvant therapy for stage I-III non-small cell lung cancer (NSCLC) is limited. This study evaluates the efficacy and safety of neoadjuvant chemotherapy alone versus chemotherapy combined with immunotherapy, focusing on pathological response, imaging outcomes, event-free survival (EFS), and adverse events. Additionally, a prognostic model for EFS is established.MethodsData from 134 NSCLC patients who received neoadjuvant therapy were analyzed. Pathological response rates, objective response rate(ORR), EFS and adverse events were compared between the two groups. Independent prognostic factors were identified using logistic and Cox regression analyses, and a predictive model was constructed and evaluated using nomograms, Receiver Operating Characteristic(ROC) curves, calibration curves, and Decision Curve Analysis(DCA) curves.Results1.The chemotherapy combined with immunotherapy group showed higher Pathological Complete Response (pCR) (48.8% vs. 12.5%) and ORR (80.2% vs. 47.9%) compared to the chemotherapy group (P < 0.05), with no difference in Major Pathological Response(MPR) or R0 resection rates. 2. Chemotherapy combined with immunotherapy group did not significantly increase TRAEs or ≥ Grade 3 TRAE rates, demonstrating acceptable safety. And incidence of immune-related adverse events (irAEs) was 20.9%, with ≥ Grade 3 irAEs at 4.3%. No treatment-related deaths occurred in neoadjuvant chemotherapy and chemotherapy combined with immunotherapy group. 3. Chemoimmunotherapy significantly prolonged EFS compared to chemotherapy alone (EFS not reached vs. 33 months, Hazard Ratio(HR)=0.45), reducing progression risk by 55% (P < 0.05).5.Pathological subtype was an independent predictor of pCR, with squamous cell carcinoma patients more likely to achieve pCR. 6. pCR and platelet-to-lymphocyte ratio (PLR) were independent prognostic factors for EFS in the chemoimmunotherapy group. The prognostic model showed good accuracy and clinical utility.ConclusionNeoadjuvant chemotherapy combined with immunotherapy significantly improves pCR rates, ORR, and EFS compared to chemotherapy alone, with manageable adverse events. The predictive model provides valuable insights for clinical decision-making.